Study guides

Q: How do you simplify the fourth root of 49?

Write your answer...

Submit

Related questions

98 is 49 times 2 so the square root of 98 is the square root of 49 times the square root of 2. But the square root of 49 is 7 , so the answer is 7 times the square root of 2.

± 2.645751

sq. root of 98 =sq. root of 49*2 =7*sq.root of 2 =7*1.414 =9.898

sqrt(245) = sqrt(49*5) = sqrt(49)*sqrt(5) = 7*sqrt(5)

7

This is clearer if you use fractional powers, at least for the intermediate steps. The fourth root of 32x2y2 is (32x2y2)1/4, or 31/2x1/2y1/2. In other words, the square root of 3xy.

sq rt(49) xa4= 7a4

Square root of 40 can be written as 49 to the power of half. So, the 2 in the half gets cancelled with the 4 leaving 49 square. And 49 square is 2401.

simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared

you cant simplify a square root

The square root of 70 can not be simplified, because the number 70 is not divisible by any perfect square (4, 9, 16, 25, 36, 49).

A square root of a negative number is not possible because there aren't two numbers that are the same that can be a negative number. Though, you can simplify it in terms of i (imaginary number), you just change it into √49 X √-1 The square root of 49 is 7 The square root of -1 is i, So it becomes 7 X i Thus making the answer 7i

simplify the square root of 300 divided by the square root of 6

The answer will depend on the form of the fourth root. Positive real numbers will have two fourth roots which are real and two that are complex. Complex numbers will have four complex roots. However, none of these can be "simplified" in the normal sense of the term.

âˆš80 - âˆš245 = âˆš(16*5) - âˆš(49*5) = âˆš16*âˆš5 - âˆš49*âˆš5 = 4âˆš5 - 7âˆš5 = -3*âˆš5

42/49

When you simplify 49 plus 37 (49+37), the result is 86.

(3 root 7) squared = (3 root 7) (3 root 7) = (3x 3) ( sq root 7 x 7) = 9 x sq root 49 = 9 x 7 = 63

147 49,3 7,7,3 The square root of 147 equals the square root of 49 times the square root of 3 which is 7 times the square root of 3.

33

49:14 = 7:2

Well, there technically is not a way to simplify the square root of 2, but the simplified version of the square root of 72 is 6 square root 2

sqrt( 147 ) = sqrt( 49 x 3 ) = sqrt( 49 ) x sqrt( 3 ) = 7 sqrt( 3 )

The square root of 49 is 7.

how do you simplify and expression of a square root